Arahan Penataan Kawasan Permukiman di Kawasan Wisata Benteng Somba Opu dengan Pendekatan Eco-Settlements - Muhammad Fahran; Mimi Arifin; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
The Somba Opu Fort Cultural Tourism Area is one of the Provincial Strategic Areas according to Regional Regulation Number 09 of 2009-2029 concerning the RTRW of South Sulawesi Province. The existence of settlements that grow around the area that is irregular and violates land use, as well as social activities of residential communities that do not support tourism activities in the Somba Opu Fort area. The Somba Opu Fort area is one of the Provincial Strategic Areas according to Regional Regulation Number 09 of 2009-2029 concerning the RTRW of South Sulawesi Province because it has a very important influence within the district on the economy, social, culture, and/or environment. The objectives to be achieved in this study are to identify the condition of settlements in the Somba Opu Fort area with eco-settlements indicators and recommend directions for revitalizing the residential environment in the Somba Opu Fort area with an eco-settlements approach. The analytical technique used in this research is descriptive qualitative analysis, and descriptive comparative analysis. The results of the analysis will later be expected to determine the condition of settlements with existing aspects so as to achieve the right direction as a reference for revitalization according to the concept of eco-settlements in settlements in the Fort Somba Opu area later.